Can Machiavellianism and Money Intentions Influence Entrepreneurial Intention? - Taboroši Srđana; Rajković Jelena; Stojanović Edit Terek; Berber Nemanja; Poštin Jasmina; Bešić Cariša; Nikolić Milan (Organizacija, 2023)
The purpose of this research is to examine how Machiavellianism and the desire for money can influence entrepreneurial intentions. It could be assumed that the desire for money and Machiavellian tendencies can develop the desire for success in people and eventually entrepreneurial intention.